Immersion Biometry for Intraocular Lens Power Calculation with Fourth-Generation Formulas - Skrzypecki J; Grabska-Liberek I; Guszkowska M; Izdebska J; Szaflik JP (Clinical Ophthalmology, 2020)
Janusz Skrzypecki,1,2 Iwona Grabska-Liberek,3 Maria Guszkowska,1 Justyna Izdebska,1 Jacek P Szaflik1 1Department of Ophthalmology, Medical University of Warsaw, Warsaw, Poland; 2Department of Experimental Physiology and Pathophysiology, Medical University of Warsaw, Warsaw, Poland; 3Department of Ophthalmology, Medical Centre for Postgraduate Education, Warsaw, PolandCorrespondence: Janusz Skrzypecki Email jskrzypecki@wum.edu.plBackground: Fourth-generation formulas for intraocular lens power calculations, including the Barrett Universal II formula, the Olsen formula or the Holladay 2 formula, were thoroughly validated with optical biometry measurements. They precisely predict the effective lens position not only in normal eyes but also in eyes with unusual anatomy. However, in the setting of dense nuclear or posterior subcapsular cataracts, optical biometers fail to obtain accurate measurements and third-generation formulas, i.e. the Hoffer Q or the SRK/T, combined with ultrasound measurements are a method of choice. Considering that optical biometry was fine-tuned to immersion ultrasound, we hypothesize that fourth-generation formulas will yield precise intraocular lens power calculations with immersion ultrasound measurements.Methods: We retrospectively analyzed 50 eyes of 50 patients who underwent uneventful cataract surgery. All patients had intraocular lens power calculated based on immersion ultrasound measurements. Refractive error predictions were compared between third-generation formulas and fourth-generation formulas.Results: There were no statistically significant differences in the median absolute error between formulas. In the study, 86%, 88%, 86%, 84%, 88% and 80% of eyes were within 1 D of target refraction for the SRK/T, the Barrett II, the Hoffer Q, the Holladay 1, the Holladay 2 and the Olsen formula respectively.Conclusion: Fourth-generation formulas combined with immersion ultrasound produced similar results to third-generation formulas. However, the percentage of eyes within 1 D of target refraction remains inferior to previously reported results for optical biometry measurements.Keywords: intraocular lens, intraocular lens power, Barrett Universal formula, cataract